2005
DOI: 10.1109/twc.2005.853834
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of linear diversity-combining schemes on Rayleigh fading channels with binary signaling and Gaussian weighting errors

Abstract: In this paper, we analyze the error probability performance of maximal-ratio combining (MRC), equal-gain combining (EGC), selection combining (SC), and generalized-selection combining (GSC) diversity schemes with coherent binary phaseshift keying (BPSK) signaling on Rayleigh fading channels with Gaussian channel-estimation errors. We first show that, with weighting errors, averaging the conditional probability of error with the density function of the instantaneous signal-to-noise ratio (SNR) at the output of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Using this expression for U(x) in (10), and substituting back in (9) and simplifying, we have (11) in (8), the probability of error for equal gain combiners over Generalized Rayleigh fading channels is…”
Section: Error Probability Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this expression for U(x) in (10), and substituting back in (9) and simplifying, we have (11) in (8), the probability of error for equal gain combiners over Generalized Rayleigh fading channels is…”
Section: Error Probability Derivationmentioning
confidence: 99%
“…Annavajjala et al [11] consider the error probability performance of MRC, EGC, SC and generalized selection combining (GSC) diversity schemes with coherent BPSK signaling on Rayleigh fading channels with Gaussian channel estimation errors. The exact probability for MRC, EGC, SC, and GSC diversity schemes with weighting errors is the same as that for the case with perfect channel estimation with average SNR per diversity branch when the in-phase correlation coefficient between the actual and the estimated channel gains is non-negative.…”
Section: Introductionmentioning
confidence: 99%
“…Some works that take into account the imperfect CSI scenario in the performance of MIMO-MRC systems can be found in [18][19][20][21][22][23]. The works in [18] and [19] analyzed the performance of MIMO-MRC systems in the presence of Gaussian channel estimation errors in i.i.d.…”
Section: Introductionmentioning
confidence: 99%
“…The works in [18] and [19] analyzed the performance of MIMO-MRC systems in the presence of Gaussian channel estimation errors in i.i.d. Rayleigh fading channels.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results on the loss in the achievable capacity of the hybrid selection MRC system due to CSI imperfections is presented in [8]. The error probability of Generalized Selection Combining is presented in [9], where it was shown that estimation errors lead to a bounded loss in Signal to Noise Ratio (SNR) compared to the perfect CSI case. The effect of channel estimation error on a MIMO OFDM system employing antenna selection is analyzed in [10].…”
mentioning
confidence: 99%